2017
DOI: 10.1039/c7cy01757j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions catalyzed by a binuclear copper complex: selective oxidation of alkenes to carbonyls with O2

Abstract: A binuclear copper complex bearing a simple salicylate ligand catalyses the efficient cleavage of styrenes into ketones and aldehydes with O2 as the oxidant. The reaction works under an atmosphere of O2 (balloon) with 0.5 mol% of catalyst and could be performed on a gram scale, providing an alternative to ozonolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…[13b,27] Alternatively, the iminium cation of 13 might be attacked by H 2 O to undergo hydrolysis reaction to give the demethylated product 4 a and formaldehyde via 15 (Scheme 6). [28] In summary, this study shows that structurally well-defined binuclear copper-salicylate complex 1 reported by us before [18][19][20] is a powerful catalyst for the aerobic oxidation of N,N-dimethylanilines. The reactions were carried out under very low loading of the binuclear copper catalyst with an oxygen balloon being sufficient in most cases.…”
Section: Entrymentioning
confidence: 58%
See 2 more Smart Citations
“…[13b,27] Alternatively, the iminium cation of 13 might be attacked by H 2 O to undergo hydrolysis reaction to give the demethylated product 4 a and formaldehyde via 15 (Scheme 6). [28] In summary, this study shows that structurally well-defined binuclear copper-salicylate complex 1 reported by us before [18][19][20] is a powerful catalyst for the aerobic oxidation of N,N-dimethylanilines. The reactions were carried out under very low loading of the binuclear copper catalyst with an oxygen balloon being sufficient in most cases.…”
Section: Entrymentioning
confidence: 58%
“…[17] Recently, we have discovered that a binuclear paddle-wheel copper salicylate complex, [Cu(Sal) 2 NCMe)] 2 (Sal = salicylate) 1, readily prepared from simple CuCl and salicylic acid as fine green crystals, can serve as effective catalyst for the aerobic cross dehydrogenative coupling of N-aryltetrahydroisoquinolines, [18] the aerobic oxidation of amines to amides with the aid of a vitamin B1 analogue, [19] as well as the selective oxidation of alkenes to carbonyls with O 2 . [20] Herein, we report that 1 could catalyze the aerobic oxidation of N,N-dimethylanilines to N-methyl-N-phenylformamides as the major products by O 2 with TBAC (tetrabutylammonium chloride) and NaBF 4 as additives, without the aid of a vitamin B1 analogue (Scheme 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the chemical methods, enzymatic methods have been explored; however, they are limited by substrate specificity (Scheme e). Following on from our recent study of aerobic cleavage of styrene derivatives with molecular iron and copper catalysts, , herein, we report that the merger of a non-heme Mn­(II) catalyst with visible light enables the oxidative cleavage of both aromatic and aliphatic alkenes under 1 atm of O 2 at room temperature (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Among catalyzed reactions we could cite, e.g. selective oxidation of alkenes to carbonyls [11,12], oxidation of aliphatic and aromatic hydrocarbons [13e20], water oxidation [21,22], CeN and CeC couplings [23e25]. No less important process, namely, the oxidative coupling of nucleophiles with arylboronic acids (Chan-Evans-Lam (CEL) coupling), is also catalyzed by copper compounds.…”
Section: Introductionmentioning
confidence: 99%